2018
DOI: 10.3897/bdj.6.e26667
|View full text |Cite
|
Sign up to set email alerts
|

New records of a critically endangered shrew from Mexican cloud forests (Soricidae, Cryptotis nelsoni) and prospects for future field research

Abstract: The Nelson´s small-eared shrew, Cryptotis nelsoni (Merriam, 1895), is a critically endangered species, endemic to cloud forests in Los Tuxtlas, a mountain range along the Gulf of Mexico coast. This species is only known from the type locality and its surroundings. Here we present new records that extend its distribution approximately 7 km southeast of the type locality and report more specimens near to the type locality. We also identified climatically suitable areas for C. nelsoni using ecological niche model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 19 publications
1
4
0
1
Order By: Relevance
“…In particular, the records of San Agustín Chayuco are notables because they are located crossing Río Verde, a large watercourse running in northern-southern direction that break the continuity of the mountains in the Sierra Madre del Sur. Maps of current potential distributions have suggested the existence of suitable conditions for cloud forest shrews in that region, but so far there were no records that corroborate its presence (Guevara et al 2015;Guevara and Sánchez-Cordero 2018). Therefore, the records analyzed here contribute to the value of these studies by corroborating their predictions.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…In particular, the records of San Agustín Chayuco are notables because they are located crossing Río Verde, a large watercourse running in northern-southern direction that break the continuity of the mountains in the Sierra Madre del Sur. Maps of current potential distributions have suggested the existence of suitable conditions for cloud forest shrews in that region, but so far there were no records that corroborate its presence (Guevara et al 2015;Guevara and Sánchez-Cordero 2018). Therefore, the records analyzed here contribute to the value of these studies by corroborating their predictions.…”
supporting
confidence: 52%
“…The lack of geographic information on species distributions (i.e., the Wallacean shortfall; Whittaker et al 2005) hinders our ability to adequately manage and conserve the natural resources of the planet. Although the scientific interest in the study of mammals has grown over the time, baseline data on the diversity and distribution of some taxonomic groups are far from well known, because biological explorations are insufficient, especially in tropical mountain regions (Guevara and Sánchez-Cordero 2018;Mayén-Zaragoza et al 2019). On the other hand, it has been observed that specimens representing new records (or even new species) have already been obtained but remain unidentified or misiden-tified in natural history collections (Kemp 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics can make it difficult for species to disperse to future suitable climatic conditions due to limited population dispersal in response to habitat fragmentation (Guevara & Sánchez-Cordero, 2018a). Moreover, many species of shrew (genus Cryptotis) are restricted to highly endangered habitats, such as montane cloud forest (Guevara & Sánchez-Cordero, 2018a, 2018b. Thus, the current con- Most species of Didelphimorphia are distributed in tropical forests (Sánchez-Cordero et al, 2014), where current deforestation rates are increasing in Mexico (Fernández-Montes de Oca et al, 2022).…”
Section: Notementioning
confidence: 99%
“…Esto ha dejado dudas sobre el estado taxonómico de ambas especies (Guevara y Sánchez-Cordero, 2018a). Por el otro lado, la diferenciación morfológica notable de C. nelsoni podría deberse a su distribución restringida en el sistema montañoso de la Sierra de Los Tuxtlas, donde la especie se encuentra aislada y probablemente sin flujo con el resto de las especies por un tiempo largo (Guevara y Sánchez-Cordero, 2018b;Woodman y Timm, 1999), incluso durante la expansión del bosque de niebla en los eventos glaciales más recientes (Guevara, 2020).…”
Section: Introductionunclassified